A Novel Round Insulated Tip Papillotome as an Alternative to the Classic Needle-Knife for Precut Sphincterotomy in Endoscopic Retrograde Cholangiopancreatography - (:unkn) unknown (HINDAWI LTD, 2015)
Objective. The purpose of this study was to investigate the efficacy and safety of a new round insulated tip papillotome (r-ITP) as compared to that of the classic needle-knife sphincterotome (NKS) in difficult-to-cannulate endoscopic retrograde cholangiopancreatography (ERCP) patients. Materials and Methods. Patients with no exclusion criteria and an intact papilla referred for ERCP were invited to participate in the study. Difficult-to-cannulate patients, defined as failure to achieve deep biliary cannulation within five minutes from the first touch of papilla, with no more than ten attempts permitted, were randomly assigned for precut sphincterotomy using either the classic NKS or r-ITP. Results. Seventy and 69 patients were randomly assigned to the NKS and r-ITP groups, respectively. The groups were comparable regarding age, sex, indications, and associated conditions. There was no statistically significant difference in terms of successful cannulation or post-ERCP complications between the two groups. Only five patients (3.6%) developed mild to moderate post-ERCP pancreatitis and two had mild bleeding. No perforations or deaths were encountered. Conclusions. Although the round insulated tip papillotome was not shown to be superior to the classic NKS concerning efficacy and safety when used by an experienced endoscopist, it remains a simple, safe, and efficacious alternative.
Keywords: POST-ERCP PANCREATITIS; CUT PAPILLOTOMY; METAANALYSIS; RISK; COMPLICATIONS; PROPHYLAXIS; SUCCESS; ACCESS